Clinical and molecular features of first two-sibling-Cambodian girls with musculocontractural Ehlers-Danlos syndrome - Sophal, Chean; Lytheang, Try; Khongkraparn, Arthaporn; Tim-Aroon, Thipwimol; Sirachainan, Nongnuch (International Journal of Contemporary Pediatrics, 2024)
Musculocontractural Ehlers-Danlos syndrome (mcEDS) is a rare autosomal recessive connective tissue disorder. To our knowledge, mcEDS has not previously been reported in Cambodia. Here, we report clinical presentations and a novel variant of CHST14 causing mcEDS in the two siblings in Cambodia. These patients from a non-consanguineous parents presented with clubfeet at birth, contractures of thumbs and feet, a typical facial appearance, and normal cognitive development. The elder sister had severe phenotypic features than the younger sister. They have been prone to ecchymosis and hematomas with minor accidents since young age, without accurate diagnosis, or confused with von-willebrand disease. Genetic consultation and confirmed by a genetic analysis revealed a novel variant, c.994-997dup, (Pro333Glnfs×23) of CHST14. Treated with oral desmopressin and daily vitamin C supplementation over 1-year-period of follow-up, the bleeding has been improved. The purpose of this article is to describe the clinical and molecular features and to show the missed or inaccurate diagnosis of this rare syndrome, which, consequently, results in suboptimal symptomatic management.